Actual Issues of Legal Assistance in Republic of Kazakhstan - AKHMETZAKIROV, Nail R.; OMAROV, Yerbol A. (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018, 2018)
Legal assistance is an integral part of the cooperation of states. As it helps to provide assistance in civil, family, criminal cases, which require execution of procedural actions in the territory of more than one country. Therefore, the authors considered and considered this important question. The main goal that the author has put before him is to determine the categories of pre-trial investigations. After the analysis of international documents, it was established that the number of cases on which the terms of the pre-trial investigation were interrupted (suspended) for the last 5 years is directly dependent on the number of instructions sent to foreign countries. In some criminal cases, the terms of the investigation are extended without taking into account the time necessary for the receipt of these cases to the law enforcement agencies of the requested state. It was determined that in relation to 11 citizens of the Republic of Kazakhstan, courts of foreign states were convicted (5 – deprivation of liberty, 4 – conditional punishment, 1 – fine, 1 – with amnesty).